PENGARUH GREEN SUKUK TERHADAP PEMBANGUNAN BERKELANJUTAN INFRASTRUKTUR HIJAU DI INDONESIA - Imanudin, Teguh; Sumengkar, Apung; Kusumaningrum, Ria (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of green sukuk issuance on the sustainable development of green infrastructure in Indonesia. Green sukuk is a sharia financial instrument used to fund environmentally friendly projects, has received attention as one of the solutions to overcome the challenges of climate change and support the development of green infrastructure. In this study, the researcher used the observation method and secondary data documentation on the website of the Directorate General of Financing and Risk Management of the Ministry of Finance (DJPPR Kemenkeu), Databoks katadata, Financial Services Authority (OJK), National Development Planning Agency (BAPPENAS), Ministry of Environment and Forestry (KLHK) which were used as primary data in this study to prove the impact of green sukuk issuance on the sustainable development of green infrastructure. This study uses a simple linear regression statistical analysis method. The results of statistical analysis were carried out using SPSS 26 software. So the equation of PBIH regression model PBIH = 4.169 + 0.026GS + e was obtained. Green sukuk affects 37.3% of the Sustainable Development of Green Infrastructure in Indonesia. Therefore, the increase or decrease in the GS variable will affect the increase or decrease of the PBIH variable because the effect is positive.